Development of a fast, automated antigen detection test for Chlamydia trachomatis - Goswami, Meghadipa (My University, 2020)
In recent years, there has been a global increase in the incidence of sexually transmitted infections (STIs) with Chlamydia trachomatis and Neisseria gonorrhoeae being the most frequent bacterial STIs. With an estimate of 106 million new infections annually, bacterial STIs cause a wide range of disorders and are a constant burden on healthcare. While there are various diagnostic methods currently in the market for STI diagnosis, their limitations have created a need for quick, affordable and sensitive STI detection and diagnosis. The mariPOC® platform utilizing two-photon excitation (TPX) technology is a rapid point-of-care (POC) device that employs separation free immunometric assay. The test system is currently used for detection of respiratory and gastrointestinal infections. POCT applications of the system are constantly expanding and are under investigation, including its use in bacterial STI testing. The main objective of this thesis was to develop a prototype test for rapid, automated detection of Chlamydia trachomatis using mariPOC® platform. In this master’s thesis, antibody binders for target C. trachomatis antigens, lipopolysaccharide and major outer membrane protein were tested. The successful binder pairs were characterized by extensive testing with purified and active infectious bacteria to study the difference in binding to epitopes. Antigen pre-treatment studies were conducted by testing extraction, mechanical disruption and urine spiking analysis for optimisation. The mariPOC® C. trachomatis test was found to be analytically 6–8 fold more sensitive compared to lateral flow (LF) assay with active infectious bacteria. Fluorescence signal from proof of concept testing of positive clinical samples was also successfully observed during the research phase. The improvement in sensitivity of C. trachomatis detection using the mariPOC® platform compared to LF, and successful testing of clinical sample proves its future potential as a diagnostic test.
Keywords: Chlamydia trachomatis, POC diagnostics, rapid testing, STI